2001
DOI: 10.1002/hyp.265
|View full text |Cite
|
Sign up to set email alerts
|

Effect of basin physical characteristics on solute fluxes in nine alpine/subalpine basins, Colorado, USA

Abstract: Abstract:Alpine/subalpine basins may exhibit substantial variability in solute fluxes despite many apparent similarities in basin characteristics. An evaluation of controls on spatial patterns in solute fluxes may allow development of predictive tools for assessing basin sensitivity to outside perturbations such as climate change or deposition of atmospheric pollutants. Relationships between basin physical characteristics, determined from geographical information system (GIS) tools, and solute fluxes and miner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 30 publications
3
17
0
Order By: Relevance
“…For example, Baron et al (1995) reported that although NH 4 + and NO 3 ) contributed to total inorganic N deposition in approximately equal amounts, NH 4 + became rapidly consumed or oxidised to NO 3 ) in the snowpack, in soils or in surface waters. Further, Sueker et al (2001) observed identical artefacts in her study and suggested that either an unaccounted-for source of NO 3 ) was present, or that nitrification was occurring. The latter conclusion was also reached by Tockner et al (2002) in their study of an Alpine glacier basin in Switzerland.…”
Section: Supraglacial Nutrient Transformations: Nh 4 Assimilation Andmentioning
confidence: 60%
“…For example, Baron et al (1995) reported that although NH 4 + and NO 3 ) contributed to total inorganic N deposition in approximately equal amounts, NH 4 + became rapidly consumed or oxidised to NO 3 ) in the snowpack, in soils or in surface waters. Further, Sueker et al (2001) observed identical artefacts in her study and suggested that either an unaccounted-for source of NO 3 ) was present, or that nitrification was occurring. The latter conclusion was also reached by Tockner et al (2002) in their study of an Alpine glacier basin in Switzerland.…”
Section: Supraglacial Nutrient Transformations: Nh 4 Assimilation Andmentioning
confidence: 60%
“…In this study, nitrate was most frequently detected in the Weminuche lakes, which are at higher elevations than lakes in the other two wilderness areas. This may reflect a lower capacity of these watersheds to retain nitrogen because of less soil coverage and steeper slopes, and lower in-lake productivity at higher elevations (Sueker et al 2001;Sickman et al 2002). Four of the Weminuche lakes did have sufficient nitrate data for trend analysis and one of those, White Dome, did show a significant upward trend in nitrate.…”
Section: Effect Of Atmospheric Depositionmentioning
confidence: 90%
“…Numerous studies have related landscape to water quality especially nutrients using empirical techniques such as correlation analysis and stepwise multiple linear regression models [7], [12]–[15], and indicated that basin physical characteristics such as land use types, morphological characteristics and local geology substantially influence the hydrology and water variables, and consequently mediate fluvial chemical compositions [10], [16], [17]. Their relative impacts on water chemistry depend on geographical scale (e.g., local, regional, national, continental and global) and sampling factors (e.g., random versus geostatistical; high versus low density).…”
Section: Introductionmentioning
confidence: 99%